PENGARUH ADVERTISING TERHADAP MINAT BELI DENGAN INTERMEDIASI PRODUCT KNOWLEDGE: STUDI EMPIRIS PADA APARTEMEN CIPUTRA WORLD SURABAYA - Pontoh, Caroline (PERFORMA, 2021)
The purpose of this research is to find out the effect of advertising on product knowledge at Ciputra World Surabaya Apartment, to find out the effect of product knowledge on purchase intention at Ciputra World Surabaya Apartment, and to find out the effect of advertising on purchase intention with product knowledge as an intermediary variable of Ciputra World Apartment Surabaya. The data collection of this research used a questionnaire that was distributed to respondents with the total sample of 40 respondents. Respondents in this research are those who domicile in West Surabaya, have income over Rp. 15,000,000 and have seen advertisement or visited the marketing office of Ciputra World Surabaya Apartment. This research uses Partial Least Square (PLS) data analysis method. The results of this research indicate that advertising affect product knowledge, product knowledge affect purchase intention and advertising affect purchase intention with product knowledge as an intermediary variable. Keyword: advertising, product knowledge, purchase intention, bounded rationality